THE INFLUENCE OF HABITAT ON THE QUALITY CHARACTERISTICS OF THE GREEN MACRO ALGA CAULERPA LENTILLIFERA AGARDH (CAULERPACEAE, CHLOROPHYTA) - Delan, Gloria G.; Legados, Julieto A.; Pepito, Ador R.; Cuñado, Venerando D.; Rica, Rachel Luz V.; Abdon, Hector C.; Ilano, Anthony S.; Lamayo, Maria Helian A. (Journal of Agriculture and Technology Management, 2018)
The seaweed Caulerpa lentillifera is commonly utilized as food for human in many Asian countries. It is an efficient bio-filter, despite its ability to absorb pollutants from the habitat of sources.This study determine the influence of habitat on the quality characteristics of the green macro alga, Caulerpa lentillifera, taken from the different sources. Purposive sampling was used with samples taken from Bohol and Cebu islands, throughout the three (3) trials. Samples from Bohol islands were obtained from the culture ponds; while samples from Cebu islands were taken from both the culture ponds and from the wild. The sea-grapes were analyzed for the presence of heavy metals, lethality assay, bacterial count, direct pollution indicators and proximate composition. Data obtained were treated statistically using ANOVA at 5percent level of significance. Results of the study showed significant difference on heavy metals (Hg and Pb) from various seaweed sources. High concentrations of heavy metals were found in all the seaweed samples from Cebu compared with that of the Bohol samples. In terms of  lethality assay (LC 50), the  wild  samples  from  Cebu  significantly  showed  higher  lethal  values  compared  with  that obtained from Bohol samples. As to the bacterial count (cfu/g), the wild samples from Cebu showed the lowest Aerobic Plate Count of 9.3 x 103   cfu/g. However, higher bacterial counts were obtained from Cebu samples that were taken from the two culture ponds co-cultured with milkfish. Across sites, the proximate composition of all the sea-grape samples from Cebu and Bohol also showed significant difference. In terms of  E. coli, all the samples have shown no significant difference, with <1.0 x 10 cfu.g-1. Regarding the indicators of direct pollution, all the samples from both islands showed low levels of direct pollutants, such as PO 4  ,   NH3, and   NO3   . Based on the results of this study, sea-grapes showed varying quality characteristics as influenced by the habitat or sources they were obtained. As a bio-filter, the quality characteristics of the seaweed are indicators of the various pollutants found from the habitat or sou rces.